The Development Of Literacy Reading Books of North Sumatera Fairy Tale For V Grade Students at Elementary School - Naomi Christina Nainggolan; Rosliani (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
The purpose of this research is to develop a literacy reading books that contain North Sumatra myth to increase passion of reading in applying literacy program in school environment. The population is all of fifth grade students of SD Kalam Kudus-2 Medan in total 109 students, and the sample is class Mikha with 29 students. Sampling technique of the research is purposive sampling, which allow researcher to determine the sample with particular consideration. The research uses the development steps of Borg and Gall which are: (1) introduction survey, (2) product development, (3) product design, (4) design validation, (5) design improvement, and (6) final product. The result of the research indicates that it is really important to develop local myth reading books for teachers and students in implementing the literacy program. These books are validated by material and learning design expert teams. The presentation of validation result by material expert is in average 82, 69% with good criteria, meanwhile by learning design expert is in average 87, 94% with very good criteria. Result that shown of Bahasa Indonesia teachers is in average 98,9% with very good criteria. In addition to small area test average is 91, 66% with very good criteria. Overall,the limited area test result is in average 95% with very good criteria.